2008
DOI: 10.1007/s00467-007-0697-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of community-acquired Pseudomonas aeruginosa urinary tract infections in children

Abstract: This retrospective chart review sought to determine clinical, radiological, and gender-associated characteristics of community-acquired Pseudomonas aeruginosa (PA) urinary tract infections (UTIs) among children admitted to two medical centers. The records of 73 children with community-acquired PA UTIs were compared with records of 109 children with community-acquired UTIs caused by other pathogens. The mean age of both groups was similar. The PA UTI group included more boys. Features significantly more common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…Female patients were reported to have a higher prevalence of UTI (60.5% female vs. 39.5% male), which is consistent with the current knowledge that anatomical and physical factors, such as a shorter urethra, predispose women to UTI [17,18]. As found in previous studies, most of the patients in the P. aeruginosa group were male [16,19,20]. Additionally, the patients with P. aeruginosa infections had higher rates of urinary tract catheter and urinary tract operation, suggesting that the P. aeruginosa UTIs were not due to preexisting diseases.…”
Section: Discussionsupporting
confidence: 78%
“…Female patients were reported to have a higher prevalence of UTI (60.5% female vs. 39.5% male), which is consistent with the current knowledge that anatomical and physical factors, such as a shorter urethra, predispose women to UTI [17,18]. As found in previous studies, most of the patients in the P. aeruginosa group were male [16,19,20]. Additionally, the patients with P. aeruginosa infections had higher rates of urinary tract catheter and urinary tract operation, suggesting that the P. aeruginosa UTIs were not due to preexisting diseases.…”
Section: Discussionsupporting
confidence: 78%
“…While Escherichia coli prevalence decreases, Pseudomonas and Proteus spp become more prominent in recurrent infections. These findings are supported by previous studies .…”
Section: Discussionsupporting
confidence: 93%
“…This novel antimicrobial mechanism is particularly effective against the P. aeruginosa , an opportunistic pathogen which causes mortality in critically ill and immuno-compromised patients [39]. Both the immunoevasive nature [54] of P. aeruginosa as well as its acquisition of multi-drug resistance [55] makes elimination of this microorganism a particular challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Its acquisition of multiple antibiobitic-resistance factors [37],[38] poses a grave challenge to drug manufacturers and patient healthcare management. Here, we found that P. aeruginosa , which thrives in local infections of the urinary tract [39], soft tissue [40], bone and joint [41], was effectively killed within 30 min in a typical infection-inflammation condition in contrast to normal condition. To determine the underlying mechanisms of the antimicrobial action, the interaction between ficolins and CRP was extensively characterized.…”
Section: Introductionmentioning
confidence: 99%